PERANAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMBUDAYAKAN DISIPLIN SISWA - Darmada, I Made (Widyadari: Jurnal Pendidikan, 2018)
This study aims to determine the discipline of students from the leadership of the principal at SMK Werdhi Sila Kumara Silakarang. The research method used is Linear Regression to predict the leadership of the principal against the discipline of SMK Werdhi Sila Kumara Silakarang students. The results of this study obtained, that the value of t count for Student Discipline variables in this study amounted to 8.497 with a significance level of 0.000 greater than t table of 1.703. This indicates that the rejection of Ho and the acceptance of Ha which means there is a significant influence of Principal Leadership variables on student discipline variables. This study has implications for the improvement of student discipline can be done through the leadership performance of the principal.